Induced pluripotency of human prostatic epithelial cells. - Hongjuan Zhao (PLoS ONE, 2013)
Induced pluripotent stem (iPS) cells are a valuable resource for discovery of epigenetic changes critical to cell type-specific differentiation. Although iPS cells have been generated from other terminally differentiated cells, the reprogramming of normal adult human basal prostatic epithelial (E-PZ) cells to a pluripotent state has not been reported. Here, we attempted to reprogram E-PZ cells by forced expression of Oct4, Sox2, c-Myc, and Klf4 using lentiviral vectors and obtained embryonic stem cell (ESC)-like colonies at a frequency of 0.01%. These E-PZ-iPS-like cells with normal karyotype gained expression of pluripotent genes typical of iPS cells (Tra-1-81, SSEA-3, Nanog, Sox2, and Oct4) and lost gene expression characteristic of basal prostatic epithelial cells (CK5, CK14, and p63). E-PZ-iPS-like cells demonstrated pluripotency by differentiating into ectodermal, mesodermal, and endodermal cells in vitro, although lack of teratoma formation in vivo and incomplete demethylation of pluripotency genes suggested only partial reprogramming. Importantly, E-PZ-iPS-like cells re-expressed basal epithelial cell markers (CD44, p63, MAO-A) in response to prostate-specific medium in spheroid culture. Androgen induced expression of androgen receptor (AR), and co-culture with rat urogenital sinus further induced expression of prostate-specific antigen (PSA), a hallmark of secretory cells, suggesting that E-PZ-iPS-like cells have the capacity to differentiate into prostatic basal and secretory epithelial cells. Finally, when injected into mice, E-PZ-iPS-like cells expressed basal epithelial cell markers including CD44 and p63. When co-injected with rat urogenital mesenchyme, E-PZ-iPS-like cells expressed AR and expression of p63 and CD44 was repressed. DNA methylation profiling identified epigenetic changes in key pathways and genes involved in prostatic differentiation as E-PZ-iPS-like cells converted to differentiated AR- and PSA-expressing cells. Our results suggest that iPS-like cells derived from prostatic epithelial cells are pluripotent and capable of prostatic differentiation; therefore, provide a novel model for investigating epigenetic changes involved in prostate cell lineage specification.